Highly hypofractionated schedules for localized prostate cancer: Recommendations of the GETUG radiation oncology group. (May 2022) - Lapierre, Ariane; Hennequin, Christophe; Beneux, Amandine; Belhomme, Sarah; Benziane Ouaritini, Nicolas; Biston, Marie-Claude; Crehange, Gilles; de Crevoisier, Renaud; Dumas, Jean-luc; Fawzi, Maher; Lisbona, Albert; Pasquier, David; et al.
Abstract: Stereotactic body radiotherapy (SBRT) has become treatment option for localized prostate cancer but the evidence base remains incomplete. Several clinical studies, both prospective and retrospective, have been published. However, treatment techniques, target volumes and dose constraints lack consistency between studies. Based on the current available literature, the French Genito-Urinary Group (GETUG) suggests that: 1. Because large prospective trials are lacking, SBRT could not be considered as a standard, but could be proposed as an option after patients have been given appropriate information and counselling. 2. Good candidates for SBRT are patients of the favorable or intermediate favorable groups. 3. 5 fractions of 7.25 Gy, for a total prescribed dose of 36.25 Gy seems both safe and effective. 4. Volume of interest delineation (target volume and organs at risk) and margins, dose constraints and radiotherapy techniques that should be used are also discussed. Highlights: SBRT cannot be considered as a standard for prostate cancer treatment as of today, but can be proposed as an option. Good candidates for SBRT are patients of the favorable or intermediate favorable groups. 5 fractions of 7.25 Gy, for a total prescribed dose of 36.25 Gy seems both safe and effective. Suggested volume of interest delineation and margins, dose constraints and radiotherapy techniques that should be used are discussed hereafter.